For a humanistic pedagogy: contemplative practices in formal educational contexts - De Simone, Mariarosaria (Formazione & insegnamento, 2018)
This work wants to explore the practices of mindfulness, which is able to promote a piece of humanistic pedagogy that places one’s global development in the core of its educational processes. The contemporary definition of mindfulness and the researches on its effetcs in formal educational settings helped to describe, on the one hand, the pedagogical movement of the Contemplative Pedagogy, on the other, a mindfulness lab carried out with university students, meant as an example of pratice.